Autobiografia e memória de Gabriel García Márquez: ficcionalização de si - Cavalheiro, Kaline (2017)
The autobiographical and self-written studies constitute a branch of the field of language studies, literature and the arts that has been increasing in recent decades. This genre of writing allows authors to reflect on the experience of writing, to trigger individual and collective memories, and at the same time to reflect on the work itself and literature. Latin American literature has been a fertile field for research with this focus, such as the work of Gabriel Garcia Marquez. The production of this genre presents us with a literary context that encompasses both critical writing and creative writing, in the texts the authors merge different styles of writing, allowing a hybrid text to appear. Reflecting on autobiographical and self-writing, the present research explores these genres where the fictional and historical merge to the example of autobiography, memory, reports, reports, interviews that reveal the subject writer. We take here the work of G. G. Márquez with the focus on the analysis of his autobiography Viver Para Contar (2002). As a complement to our analysis, in the scope of fictional writing we have the works A incrível e triste história da Cândida Erêndira e sua avó desalmada (1972), Relato de um Náufrago (1970) and Crônica de uma Morte Anunciada (1981) that contemplate aspects of Autobiography, collective memory and explore the data from the Colombian context and history. The study of these texts allows us to verify how G. G. Márquez re-elaborates the historicity of his time in the fictional works. From the readings and analyzes, we carried out a reflection on the potential of the autobiographical or self-written, together with the fictional texts, to understand the Latin American historical context and the role of intellectuals who have lived the history of Latin American dictatorships and Who had to reinvent themselves and reelabor strategies of writing and the expression of thought. Our contribution with the present research is that in observing the writing process of G. G. Márquez, we verified that there is a fusion and why not to say juxtaposition between the categories author, character and narrator in the confluence between autobiography, memory and fiction, by what we call autowriting , Being precisely this way of narrating quite expressive in the work of G. G. Marquéz. The theme of this dissertation proposes to reflect on the imbricated relationship between history and literature in the author 's work, a fabric that reveals several layers of the real, imagined, official history and personal memory. It attempts to present the author not only as a constructor of the literary work, but as a constructor of a critical thinking articulating work, social life and contemporary cultural practices together with his hybrid writing that goes from the real to the imaginary, memorialistic, historical, critical , Among other genres that are approaching. In order to carry out this study we reflect on the theories of autobiographical constructions, starting from the definitions of Philippe Lejeune (2008), deepening this theoretical basis, we advance to other approaches, like Paul Ricoeur (2007), Diana Klinger (2012), among others. These theoretical approaches illuminate the corpus selected for this research, as the self-writing in the process of reworking personal memory and the movement of history and its context captured.